Modern Trends of Radiotherapy Cancer Oral Cavity - V. A. Titova; G. P. Snigireva; V. Y. Petrovsky; E. N. Telisheva (Сибирский онкологический журнал, 2016)
Growth of frequency of squamous cell cancer of oropharynx and dominance of locally-spread forms of a tumor at 60 % with the early infiltrative growth and metastasis in regional lymph nodes reduce results of treatment to 40 %. The combination in a uniform course of treatment of operation, radiation therapy and chemotherapy doesn’t exclude risk the lokoregional of a recurrence at 30–60 % and at 18 % – isolated metastases. At patients at the age of 50 years with cancer of oropharynx 5 years treatment doesn’t exceed 40 %. At the same time switching on in programs of radiation and combined treatment with chemotherapy (CT) increases effectiveness of traditional methods to 69 %. New technologies of conformal radiation therapy (CRT); HDR brachytherapy with the radio modifying agents and PHT, including target drag – are implemented everywhere in case cancer of oropharynx. However CRT 66–70 Gr provides local control in case of 5–10 years’ observation only at 57 %; lokoregion – 50 % with the overall (OS) survival – 47 % and 35 %, respectively. There are data on detection of mutations in EGFR gene in case of malignant diseases of an oral cavity and throat. Directional application the target drag – EGFR blockers, for example a cetuximab (erbitux) in the first line of therapy of planocellular cancer of the head and neck increases survival indices. On the other hand, the raised expression of a gene of EGFR can correlate with progressing of a disease and the poor results. The aim: to provide new technologies of CRT with brachytherapy 192Ir and chemotherapy of 30 patients with cancer of cancer of oropharynx with assessment of presence of retrospectively probed mutation at EGFR gene. Results of CRT and HDR brachytherapy depended on tumor localization in oral cavity, a stage and prevalence of process, prognostic factors and treatment. CRT improved results of multimodal treatment and quality life of patients: the OS is reached at 100 % of patients with cancer of a lip; 66,7 % of patients with cancer of tongue and 75 % of cancer mouth bottom. EGFRvIII weren’t revealed in one of analysed samples of tumor. The positive effect from target therapy erbitux wasn’t registered at one of two treated patients without mutations of EGFR.